MALIGNANCIES DETERMINED BY UPPER GASTROINTESTINAL SYSTEM ENDOSCOPY IN 1400 CASES - Tülay SARIÇAM; Eser VARDARELİ; Ayşegül HARMANCI; Yekta KIŞIOĞLU; Nur KEBAPÇI; Esat ERENOĞLU (Turkish Journal of Gastroenterology, 2020)
-